Isolation methods influence the biological properties of Wharton’s Jelly-derived mesenchymal stem cells: A comparative study of yield, viability, proliferation, differentiation potential, and proteomic profiles - Jens Long Nguyen; Samih Mohamed-Ahmed; Ragda Saleem; Kamal Mustafa; Niyaz Al-Sharabi; Mariann Haavik Lysfjord Bentsen (PLoS ONE, 2026)
Background Mesenchymal stem cells derived from Wharton’s Jelly (WJ-MSCs) are an attractive cell source for regenerative medicine due to high proliferative capacity, non-invasive accessibility, and minimal ethical constraints. However, their therapeutic efficacy may vary with isolation technique and culture conditions. Methods We compared three WJ-MSC isolation methods; two explant approaches (non-scraped and scraped) and one enzymatic method – each cultured with or without basic fibroblast growth factor (bFGF). WJ-MSCs were obtained from three full-term umbilical cords, and subsequently evaluated for cell viability, proliferation kinetics, immunophenotypic surface marker expression, multilineage differentiation potential, and proteomic profiles through mass spectrometry coupled with bioinformatics analyses. Results All methods produced viable WJ-MSCs, although enzymatic isolation without bFGF resulted in early culture failure in 2/3 donors and was excluded from downstream analyses. Highest viability was observed with the non-scraped explant method supplemented with bFGF, and bFGF significantly enhanced proliferation by reducing cell doubling time. All groups consistently expressed canonical MSC markers, along with WJ-MSC-specific surface proteins. Osteogenic differentiation was robust across all groups, whereas adipogenic differentiation was limited. Proteomic profiling revealed 2,372 proteins commonly expressed across all groups, indicating a largely stable core proteome, with isolation- and bFGF-dependent modulation observed primarily at the pathway level. Gene set enrichment analysis showed that bFGF-treated cultures were enriched for metabolic pathways, including oxidative phosphorylation and fatty acid metabolism, whereas bFGF-free and enzymatic isolation methods showed increased inflammatory and stress-related signatures. Differential expression analysis further identified 36 proteins uniquely regulated by isolation method and bFGF treatment, associated with cell adhesion, tissue morphogenesis, and immunomodulatory functions . Conclusion This study clarifies how isolation- and growth factor–driven effects shape the functional properties and paracrine identity of WJ-MSCs. The non-scraped explant method with bFGF emerges as a robust, reproducible approach, yielding high-viability, phenotypically stable, and metabolically resilient MSCs. These findings provide a framework for standardized WJ-MSC production optimized for regenerative and immunomodulatory applications.